Australia-SH Antigen in Hepatitis Patients in London. Issue 5673 (27th September 1969) - Cossart, Y.; Taylor, P. E.; Vahrman, J.; Zuckerman, A. J.
Abstract : Australia-SH antigen was found in 11 out of 27 sera (40%) obtained from patients with acute viral hepatitis soon after their admission to hospital. Six out of 11 positive sera were collected within the first 12 days of illness; die remaining five were collected between the 13th and 30th days. The antigen was detected by immunodiffusion in agarose gel, five different indicator sera containing Australia-SH antibodies being used. The specificity of these sera was found to be very similar. All of the patients' sera were examined independently by two separate laboratories. The results obtained by the laboratories were in close agreement, though the techniques varied in detail.